The effect of E-homework on K-12 students’ academic achievements: a meta-analysis study - Yang, Zhiping; Yu, Yating; Chen, Ruyi (Frontiers in Psychology, 2026)
Although E-homework has gained increasing popularity with the digital transformation of education, its actual effectiveness remains widely debated in academia. This study employed a meta-analysis to comprehensively evaluate the impact of E-homework on K-12 students’ academic achievements based on experimental research conducted between 2000 and 2025. Literature was sourced from Chinese databases (CNKI, Wanfang, etc.) and English databases (Web of Science, Science Direct, etc.), resulting in the inclusion of 26 empirical studies that met predefined criteria. In addition to the overall effect analysis, subgroup analyses were conducted. The results revealed a significant positive effect of E-homework on academic achievement, with an overall effect size of Hedges’ g = 0.309. Subgroup analysis further indicated that the enhancing effect of E-homework was more pronounced on assignment scores compared to exam scores. Furthermore, both subject domain and school level were found to moderate the effectiveness of E-homework.